A Gendered Identity Debate in Digital Game Culture - Lotte Vermeulen; Mariek Vanden Abeele; Sofie Van Bauwel (Press Start, 2016)
Although women make up half of the gamer population, only a small portion of them considers themselves as a gamer. This is seen as a logical consequence of a culture and industry that fiercely concentrate on legitimizing a masculine gamer identity. The upcoming presence of women in the digital game landscape, however, is threatening the notion of the masculine gamer. The aim of the current article is to analyze this threat, and how new forms of backlash emerge in response to it. Drawing from social identity and feminist theory, we argue that these new forms of backlash can be understood as  ‘identity management strategies’, aimed at protecting masculine gamer identity. We analyze three such strategies: (1) the use of novel gendered binaries to frame the masculine against a feminine gamer identity, (2) the use of hostile sexist assaults to silence feminist gamers and advocates, and (3) the use of dualistic postfeminist discourses to mitigate and undermine criticisms.